194k views
1 vote
Evaluate - 2y + x(-3)
When x = -5 y = 3

2 Answers

3 votes
Try seeing the problem as
-2(y) + x(-3)
If you plug in 3 in place of y, you’ll get
-2(3) + x(-3).
If you solve the first half of the equation, you’ll be left with
-6 + x(-3)
Repeat this step with x, by plugging in -5 in place of x
-6 + -5(-3)
A positive * a positive = a negative, so your equation should look like
-6 + 15
If you flip it around, you’ll be left with a simple problem, and answer
15 - 6 = 9


User Fuzzyman
by
4.6k points
6 votes

Answer:

27

Explanation:

2(6) + -5(-3)

= 12+15

= 27

User Farm
by
4.8k points